Cybersecurity - Review, Harvard; Blau, Alex; Burt, Andrew; Groysberg, Boris (Ascent Audio, 2019)
No data is completely safe. Cyberattacks on companies and individuals are on the rise and growing not only in number but also in ferocity. And while you may think your company has taken all the precautionary steps to prevent an attack, no individual, company, or country is safe. Cybersecurity can no longer be left exclusively to IT specialists. Improving and increasing data security practices and identifying suspicious activity is everyone's responsibility, from the boardroom to the break room. Cybersecurity: The Insights You Need from Harvard Business Review brings you today's most essential thinking on cybersecurity, from outlining the challenges to exploring the solutions, and provides you with the critical information you need to prepare your company for the inevitable hack. The lessons in this book will help you get everyone in your organization on the same page when it comes to protecting your most valuable assets.